Entrepreneurship Curriculum In Higher Education: A Systematic Literature Review (SLR) - Yori Andes Saputra; Fitri Novilia; Heny Hendrayati (West Science Interdisciplinary Studies, 2023)
Entrepreneurship education at the higher education level plays an increasingly crucial role in shaping graduates who are not only ready to enter the workforce but also capable of becoming independent entrepreneurs. While many university graduates aspire to pursue careers in office jobs or work for other institutions, it is important to realize that entrepreneurial skills have a positive impact not only on individuals but also on the economy and society as a whole. In this context, entrepreneurship education in higher education becomes key to shifting the paradigm of graduates towards being more proactive and independent in creating job opportunities. Currently, many countries face challenges in creating new job opportunities and reducing unemployment rates. Therefore, introducing the concept of entrepreneurship into the higher education curriculum can be a strategic step to address these issues. Graduates with a strong understanding of entrepreneurship will not only be job seekers but also job creators. They have the potential to establish their own businesses, create new products or services, and make a positive contribution to the local and national economic development. Through entrepreneurship education, students can be equipped with practical skills, business knowledge, and a proactive attitude needed to become leaders in the business world. Moreover, it is essential to address any stigma attached to the development of entrepreneurship in higher education, where many students may be more inclined to choose conventional career paths. By recognizing the importance of entrepreneurship in creating new opportunities and enhancing competitiveness in the job market, universities can play a key role in inspiring and guiding students to explore their entrepreneurial potential. Thus, entrepreneurship education at the higher education level is not just about creating entrepreneurs; it is also about shaping individuals who have a proactive outlook on their lives and careers and the ability to adapt and thrive in a dynamic work environment. Entrepreneurship education in higher education has a significant long-term impact on shaping a more competitive and innovative future.